Strategic Approach to Drive Business Growth in The Food and Beverage Industry: Study Case: Bahagia Kopi - Pradewa, Adib Putra; Dhewanto, Wawan (Economics and Business Journal (ECBIS), 2025)
The Indonesian coffee industry continues to grow rapidly, increasing competition among businesses. Bahagia Kopi faces challenges in slowing sales growth and stagnant asset expansion, requiring a strategic approach to sustain long-term growth. This study evaluates Improvement and Scaling as the most suitable growth strategies, using a mixed-method approach that integrates semi-structured interviews and quantitative analysis through the Analytic Hierarchy Process (AHP) and financial assessment. In the short term, operational efficiency and service quality improvements are the main priorities, requiring investment in training and performance-based incentives. In the long term, branch expansion in Bandung is identified as the key growth initiative, with funding as the primary challenge since Bahagia Kopi still depends on internal capital. Financial analysis of 2023 reports shows increased profitability, but a 32% funding shortfall remains for expansion. To address this, Mixed Financing is the most balanced approach, maintaining a healthy solvency ratio while minimizing financial risk. With a cautious yet strategic approach, Bahagia Kopi can achieve sustainable expansion without overleveraging debt, ensuring long-term stability and maintaining business growth